2014
DOI: 10.4103/0973-1482.136566
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Computerized Tomography density patterns of lymph nodes with treatment results and outcome in head and neck cancer patients treated by 2 different chemoradiotherapy schedules

Abstract: No statistically significant association between recovery and CT density was found (X 2 = 0.306; P > 0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Intranodal necrosis is visualized on CT as a non-enhancing hypodense area, and such necrotic areas are thought to contain less oxygen and have poorer responses to chemotherapy or radiotherapy. Some studies showed that hypodense metastatic nodes on contrast-enhanced CT had a significantly poorer response to chemotherapy or chemoradiotherapy compared to isodense metastatic nodes [11,12,23], while other studies did not [13,24]. Such inconsistent results may be attributed to the fact that not all the hypodense metastatic nodes were necrotic, as some may have been cystic nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Intranodal necrosis is visualized on CT as a non-enhancing hypodense area, and such necrotic areas are thought to contain less oxygen and have poorer responses to chemotherapy or radiotherapy. Some studies showed that hypodense metastatic nodes on contrast-enhanced CT had a significantly poorer response to chemotherapy or chemoradiotherapy compared to isodense metastatic nodes [11,12,23], while other studies did not [13,24]. Such inconsistent results may be attributed to the fact that not all the hypodense metastatic nodes were necrotic, as some may have been cystic nodes.…”
Section: Discussionmentioning
confidence: 99%